Fabrication and characterisation of filled Polyvinyl Alcohol (PVA): Sago Starch Acetate and Microcrystalline Cellulose (MCC) / Nada Syahifah Mohd Ali - Mohd Ali, Nada Syahifah (2008)
The research was conducted to fabricate Polyvinyl Alcohol (PVA) filled Sago Starch Acetate film and mixtures in water to solve problem of adverse impacts on the environment to replace polyolefin film used in agricultural mulch film. This research will investigate the effect of the PV A/Sago Starch Acetate (SSA) film and Microcrystalline Cellulose incorporation which recently is known to increase mechanical performance of plastics. Determination of thermal and mechanical properties of PVA: Sago Starch Acetate formulation with and without MCC was investigated. PVA were subsequently mixed in water with Sago Starch Acetate at various proportions with amount of constant MCC. Microcrystalline Cellulose is added to determine its effect on strength of filled PVA. . In this research the thermal properties of these blends were determined by Differential Scanning Calorimetry (DSC), which indicates the presence of two and more separate phases of sago starch and PVA. The mechanical properties were determined by Testometric Tensile Machine. The physical properties were determined by water absorption test. The viscosities of mixture were determined by Brookfield Viscometer. The highest viscosity will be obtain with the lower SSA of gelatinized sample and the lowest viscosity is the sample non gelatinized of PV A/Sago Starch Acetate with highest SSA percentage. Increase in Sago Starch Acetate resulted in lower tensile strength and modulus. While MCC has proved to provide resisting force effect of tension. MCC provide site for strengthening in each blend samples. Tm will decrease with the increased SSA percentage. The water absorption of these blends is quite high, so this behaviour makes the blends appropriate for mulch film. Hence , with use of MCC, material can assimilate through soil and can be suitable for mulch film as material can be discarded accordingly.